ANALYSIS OF LIVABLE STREET AT HOS. COKROAMINOTO STREET CORRIDOR AS A PUBLIC SPACE IN PONOROGO REGENCY - Hilba Yoga Pratama; Agung Budi Sardjono (Jurnal Arsitektur ARCADE, 2023)
Abstract : Public space in an urban area has an important role to improve the quality of life for the general public. Public space in the form of street corridors is a very important element in the infrastructure system of a region or city. A street corridor in an urban area does not only function as a mobility lane for vehicles, but can also function as a forum for community activities, and can create a unique identity for an area. The Hos. Cokroaminoto street corridor in Ponorogo Regency is one of the street that is often used by the Ponorogo Regency Government to hold several cultural events, in this street corridor the general public also carries out social and commercial activities. The purpose of this study is to explain the quality of the Hos. Cokroaminoto street corridor as a public space which is reviewed from several aspects in the form of physical and non-physical aspects, as well as activities that are created by identifying their linkages with existing facilities. The research method uses descriptive qualitative, by presenting an overview regarding the real condition of the street corridor, and findings about the existing conditions in an effort to create a "Livable Street" public space. Data were obtained through observation, interviews with street corridor users and the local government, as well as from related literature studies. The results of the study provide an explanation of the level of comfort and safety in the Hos. Cokroaminoto street corridor as a â€œLivable Streetâ€ public space.Keyword : Livable Street, Public Space, Hos. Cokroaminoto Street Corridor.Abstrak : Ruang publik di suatu kawasan perkotaan mempunyai peranan penting dalam meningkatkan kualitas hidup masyarakat luas. Ruang publik berupa koridor jalan merupakan elemen yang sangat penting dalam sistem infrastruktur suatu wilayah atau kota. Koridor jalan pada suatu kawasan perkotaan tidak hanya berfungsi sebagai jalur mobilitas kendaraan saja, namun juga dapat berfungsi sebagai wadah beraktivitasnya masyarakat, serta dapat menciptakan identitas unik suatu kawasan. Hos. Koridor jalan Cokroaminoto di Kabupaten Ponorogo merupakan salah satu jalan yang sering digunakan oleh Pemerintah Kabupaten Ponorogo untuk menyelenggarakan beberapa acara kebudayaan, di koridor jalan ini masyarakat umum juga melakukan kegiatan sosial dan komersial. Tujuan dari penelitian ini adalah untuk menjelaskan kualitas Hos. Koridor jalan Cokroaminoto sebagai ruang publik ditinjau dari beberapa aspek berupa aspek fisik dan non fisik, serta aktivitas yang tercipta dengan mengidentifikasi keterkaitannya dengan fasilitas yang ada. Metode penelitian yang digunakan adalah deskriptif kualitatif, dengan menyajikan gambaran mengenai kondisi riil koridor jalan, dan temuan mengenai kondisi eksisting dalam upaya mewujudkan ruang publik â€œJalan Layak Huniâ€. Data diperoleh melalui observasi, wawancara kepada pengguna koridor jalan dan pemerintah setempat, serta studi literatur terkait. Hasil penelitian memberikan penjelasan mengenai tingkat kenyamanan dan keamanan di Hos. Koridor jalan Cokroaminoto sebagai ruang publik â€œLivable Streetâ€.Kata Kunci : Jalan Layak Huni, Ruang Publik, Hos. Koridor Jalan Cokroaminoto.